Ticks (Acari: Ixodidae) and lice (Phthiraptera: Trichodectidae) infesting free-living coatis (Nasua nasua Linnaeus, 1766) with sylvatic and synanthropic habits in the Atlantic rainforest of Southern Brazil - Magalhães-Matos, Paulo C.; Moraes, Marcela F. D. [UNESP]; Valim, Jaqueline R. A.; Castro, Gustavo N. S.; Santos, Priscilla N.; Manier, Bruna S. M. L.; Fonseca, Adivaldo H. (Systematic and Applied Acarology Society, 2017)
This research describes the infestation by ticks and lice in free-living coatis (Nasua nasua Linnaeus, 1766) with sylvatic and synanthropic habits living at the Iguaçu National Park (INP), state of Parana, southern Brazil. During the months of September 2014 and from March to April 2015, ticks and lice were collected from 86 free-living coatis from INP. Among the animals analyzed, 99% (85/86) were infested with ectoparasites, Amblyomma spp. larvae (n=23), nymphs of Amblyomma brasiliense (n=77), Amblyomma coelebs (n=427) and Haemaphysalis juxtakochi (n=6) being observed, as well as Amblyomma ovale adults (n=46). Lice were found in lower prevalence (13%, 11/86), nymphs (n=31) and adults (n=9) of Neotrichodectes pallidus. Summary results show feral coatis with sylvatic and synanthropic habits as competent hosts for ixodid ticks and lice, arthropods responsible for the transmission of pathogens for carnivores, others wildlife and humans. This paper presents the first record of H. juxtakochi infesting coatis in Brazil.
Keywords: Atlantic forest; Brazil; Iguaçu National Park; lice; Procyonidae; Ticks